Performance Audit as Forensic Examination in Intentional Bankruptcy Cases - Tumaitytė, Asta; Daujotaitė, Dalia (Buhalterinės apskaitos teorija ir praktika, 2018)
[only abstract in English; full article and abstract in Lithuanian]The article focuses on the performance audit as forensic examination in intentional bankruptcy problems experienced by the Lithuania. One of possible areas of performance audit expansion is a forensic examination, which is backed by various similarities – qualification requirements, the type of work being done by the expert/auditor, as well as it also taps into the essence of performance audit: to assure the effectiveness (which in this type of application is expressed via efficient litigation process).Since performance audit does not have the time proven place in civil proceedings, this article strives to bring attention of scientists and practitioners to the possibilities of application of performance audit as a forensic examination in the process of intentional bankruptcy. Cases of intentional bankruptcy are specific by its origins due to the circumstances of occurrence of bankruptcy itself: because it is intentional, financial statements of legal entity might not be indicating mala fide, therefore, financial audit might not be capable of detecting the inappropriate actions of management. Performance audit might become a key to solving this deficiency.This article utilises analysis of scientific literature as well as available (current and historical) court practice in Lithuania, seeking to provide an insight into – not only theoretical, but also practical –advantages that can be gained from performance audit examination in intentional bankruptcy cases.By interpreting, the law and analysing the content of the court decisions, the conclusion is being made that with the condition of proper qualification assurance performance audit examination might speed up the proceedings of the intentional bankruptcy and provides qualified factual evaluation for the court, hence making litigation process more efficient. It could also save time and expenses for both – court system (hence – the State) and involved parties. It would also help increase public trust and reliability of judicial system and its capability to effectively restore the clarity of economic relations between parties involved.